Medicinal plants used in multiple sclerosis patients, prevalence and associated factors: a descriptive cross-sectional study - Naemeh Nikvarz; Behnaz Sedighi; Mehdi Ansari; Shirin Shahdizade; Reyhane Shojaei; Fariba Sharififar (BMC, 2024)
Abstract Introduction Multiple sclerosis (MS) is a chronic and debilitating disease that not only leads to disability and associated condition but also impacts one's ability to maintain a professional life. People's acceptance and utilization of medicinal plants (MPs) play an important role in managing their treatment process. As a result, this study aims to investigate the use of medicinal herbs among patients with MS. Methods A descriptive cross-sectional study was conducted on 150 MS patients who visited a private clinic and the MS Association in Kerman, Iran in 2021. A questionnaire comprising questions about sociodemographic information, disease variables, and aspects of MPs usage was utilized for data collection. Statistical analysis was performed using SPSS version 20 (SPSS Inc., Chicago, IL). The Chi-square test was employed to identify any association between demographic characteristics and MPs usage. To determine the prevalence of plant use in a specific area and the consensus among informants, the use value (UV) and Informant consensus factor (Fic) were calculated. Results The study revealed a high prevalence of MPs usage among MS patients. Chamomile (66.6%) and golegavzaban (62.0%) were the most commonly used plants with the highest UV indices (0.88 and 0.82 respectively), while St. John's wort and licorice were rarely used (0.67% and 4% respectively). Participants cited pursuing a healthier lifestyle as the primary reason for using MPs (24%). St. John's wort, lavender, and chamomile were the most satisfying plants (100%, 100%, and 53.0% respectively). Chamomile had the highest Fic too. Most patients were motivated to get MPs from their relatives. Conclusions Given the widespread use of MPs among MS patients, neurologists should enhance their knowledge in this area to guide patients away from seeking advice from non-professionals. Providing standardized formulations can help prevent potential interactions between MPs and mainstream drugs, thereby improving patients safety and outcomes.